(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The present research is framed to study the reflection of society in the plays and literatures of Henrik Johan Ibsen. The plays which depicts the convictions and culture of society in the period of 19th century. The aim of this study is to highlight the use of societal conventions in the plays of Henrik Ibsen to bring the realism in the world of theatre. This research tends to focus on the intension of reflecting realism in the work of Ibsen. It advocates the change Ibsen wants to see in the society which is why he never missed any single chance to mention about the limitation’s society has imposed on people through different ways.